Model Komunikasi Bisnis Dalam Berwirausaha Kuliner Pasca Pandemi Covid-19 Pada Umkm Kota Depok (Cakrawala - Jurnal Humaniora, 2024)
This research aims to analyze an effective business communication model in the context of culinary entrepreneurship post the COVID-19 pandemic, particularly in Micro, Small, and Medium Enterprises (MSMEs) in Depok City. The COVID-19 pandemic has significantly impacted the culinary sector, with social restrictions and changes in consumer behavior. Therefore, it is crucial to understand how culinary MSMEs can adapt and succeed in facing these challenges. This study employs a qualitative approach, utilizing in-depth interviews with culinary MSME owners in Depok City. The data collected are analyzed using thematic analysis to identify emerging patterns and findings. The research findings indicate that an effective business communication model for culinary MSMEs post the COVID-19 pandemic involves several key elements. Firstly, MSMEs need to have a clear and targeted communication strategy, including identifying the appropriate target market and developing relevant messages. Secondly, the utilization of digital and online media is crucial in promoting products and reaching potential consumers. MSMEs need to leverage social media, websites, and online booking platforms to enhance product visibility and accessibility. Furthermore, collaboration with relevant stakeholders is also an essential factor in a successful business communication model. MSMEs can establish partnerships with local suppliers, culinary communities, and government institutions to expand their reach and gain necessary support. This research provides valuable insights for culinary MSMEs in Depok City and similar sectors in developing effective business communication models post the COVID-19 pandemic. By adopting these approaches, MSMEs can enhance their chances of success in facing challenges and capitalizing on emerging opportunities amidst changing consumer behavior and intensifying competition in the post-pandemic era.